Too little, too slow: an analysis of 2022’s developments in the EU’s migration and asylum policy - Mazur, Sylwia K. (2023)
Migration and asylum are two of the most challenging issues in Europe. With every crisis, new shortcomings are exposed. However, actions taken by the European Union and its Member States have proven that common migration and asylum policy remains a distant goal. In the presented paper, the author analyses developments in the European Union migration and asylum policy of 2022, stating that, despite the momentum caused by the support given to Ukrainians with temporary protection, hopes for comprehensive asylum and migration policy reform should be toned down, despite the end of the legislative period looming on the horizon.